The Effect of particulate matter on visibility in Hangzhou, China - Cheng, Wen; Lu, Huijian; Shi, Yao; He, Yi (2018)
Hangzhou, a humid subtropical city of China, was studied to investigate the effect of particulate matters (PMs) and its fractions (e.g., PM2.5 and PM2.5~10) and levels of relative humidity (10 to >90%) on atmospheric visibility. It was found that finer fractions of PM have greater negative effect on visibility. This inverse relationship was pronounced during winter season, having the highest PM2.5 concentrations and the lowest visual range. Summer season exhibited the highest visual range and least PM2.5 fractions, along with autumn. Furthermore, lower relative humidity coincides with higher visual range regardless of the PM fractions. As the levels of relative humidity went up (>90%), lower values of visual range were measured. The results from this study suggest that lower target levels of PM2.5 is needed for Hangzhou in order to prevent episodes of poor visibility.
Keywords: Visibility; Particulate matter